A novel BiOCl (110)/rGO/Ag3PO4 (111) heterostructure for efficient detoxification of 2, 4-dichlorophenol. (December 2022) - Li, Jie; Li, Yi; Wu, Haisuo; Naraginti, Saraschandra; Chen, Pengli; Chen, Yang
Abstract: An effective method using nontoxic and efficient photocatalysts are crucial for wastewater treatment. Bismuth oxychloride (BiOCl) is considered as one of the valuable photocatalysts due to its unique layered plate like structure, however higher recombination and unsatisfied visible light absorption efficiency seriously affecting its applications. Addition of tetrahedral silver phosphate (Ag3 PO4 ) which is known for its superior photocatalytic efficiency under visible light is believed to be the solution for the issue. Upon further adding of reduced graphene oxide (rGO) could form a bridging structure and enhance the activity. Considering the merits of these materials the BiOCl (110)/rGO/Ag3 PO4 (111) heterojunction has been successfully constructed for 2, 4-dichlorophenol (DCP) enhanced detoxification. The efficiency in degradation was found to be 94.8% by BiOCl/rGO/Ag3 PO4 (k = 0.01879 min −1 ) that was greater to that of pure Ag3 PO4 (∼1.9 times; k = 0.00818 min −1 ) and pure BiOCl (∼2.8 times; k = 0.00642 min −1 ) after 60 min of visible light irradiation. The mechanism of degradation was explained through the principle of heterojunction energy-band theory. Furthermore, 2, 4-dichlorophenol (2, 4-DCP) degradation products identification was carried out by ESI/LC-MS to propose the degradation pathway. Furthermore, the phytotoxicity of the intermediate products was investigated by estimating the germination index (GI) values on Phaseolus vulgaris ( P. vulgaris ) at different time intervals and the GI values were found to be 10.79% and 80.17% before and after degradation respectively. Thus, our results revealed that efficient and significant toxicity reduction was observed in this photodegradation. Graphical abstract: Image 1 Highlights: BiOCl (110)/rGO/Ag3 PO4 (111) composite was prepared by a facile method. Photo-corrosion of Ag3 PO4 was reduced efficiently by rGO/BiOCl. Increased Germination Index (GI) was observed during degradation. Efficient detoxification of 2, 4-dichlorophenol was attained by this composite.